2017
DOI: 10.6007/ijarafms/v7-i1/2613
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Electronic Service Quality on Customers Satisfaction of Islamic Banks in Jordan

Abstract: The study aimed to study impact of Electronic Service Quality on Customers Satisfaction of Islamic Banks in Jordan. The Electronic Service Quality represented by (Reliability, Ease of use, Effectiveness, Web Site Design, privacy, and Responsiveness). The population of the study consisted customers of Islamic banks in the North territory of Jordan (Jordanian Islamic Bank, International Arab Islamic Bank), a random sample was taken amounted (300) participants, SPSS was used to examine the study hypotheses and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 32 publications
(56 reference statements)
2
19
0
2
Order By: Relevance
“…The findings displayed that credibility and usefulness ensure positive impact while cost and ease of use are less important. Moreover, Al‐Hawary and Al‐Smeran (2017) studied the effects of E‐service on the satisfaction of Islamic Banks customers of Jordan. A random sample of 300 respondents was selected.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…The findings displayed that credibility and usefulness ensure positive impact while cost and ease of use are less important. Moreover, Al‐Hawary and Al‐Smeran (2017) studied the effects of E‐service on the satisfaction of Islamic Banks customers of Jordan. A random sample of 300 respondents was selected.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…The results of this study are appropriate, that the online transaction experience affects the satisfaction of independent transaction services. [30]. Digital wallet application makers have to think about hundreds or even thousands of possibilities that will happen when users perform self-service activities.…”
Section: Discussionmentioning
confidence: 99%
“…Also the Availability, Security, Reliability and Fulfillment are direct impact but personalization has no effect on customer satisfaction (Asadpoor & Abolfazli, 2017). Al-Hawary & Al-smeran (2017) found that the Electronic Service Quality (Ease of use, Web Site Design, privacy, and Responsiveness) affected Customers' Satisfaction of Islamic Banks in Jordan (Al-Hawary et al, 2017). Addai, Bismark, Eric & Quaye (2015) by a multiple regression analysis showed that there is a positive correlation between customer satisfaction and e-baking availability, reliability and convenience in the selected banks in Ghana (Addai et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 98%